Alzheimer’s Disease Polygenic Risk Score Is Not Associated With Cognitive Decline Among Older Adults With Type 2 Diabetes - Manzali, Sigalit B.; Yu, Eric; Ravona-Springer, Ramit; Livny, Abigail; Golan, Sapir; Ouyang, Yuxia; Lesman-Segev, Orit; Liu, Lang; Ganmore, Ithamar; Alkelai, Anna; Gan-Or, Ziv; Lin, Hung-Mo; et al. (Frontiers in Aging Neuroscience, 2022)
Objectives:Multiple risk loci for late-onset Alzheimer’s disease (LOAD) have been identified in recent years. Type 2 diabetes (T2D) is a risk factor for cognitive decline and dementia, including Alzheimer’s disease. We investigated the association of polygenic risk score (PRS) for LOAD with overall cognitive functioning and longitudinal decline among older adults with T2D. Methods:The study included 1046 Jewish participants (aged≥65 years) diagnosed with T2D, who were cognitively normal at baseline. The PRS included variants from 26 LOAD associated loci (at genome-wide significance level), and was calculated with and without APOE. Outcome measures, assessed in 18-months intervals, were global cognition and the specific domains of episodic memory, attention/working memory, executive functions, and language/semantic categorization. Random coefficient models were used, adjusting for demographic variables, T2D-related characteristics, and cardiovascular factors. In a subsample of 202 individuals, we analyzed the association of PRS with the volumes of total gray matter, frontal lobe, hippocampus, amygdala, and white matter hyperintensities. Last, in 44 participants who underwent an F18-PET scan, we examined the association of PRS with amyloid beta (Aβ) standardized uptake value ratio. Results:The PRS was not significantly associated with overall functioning or rate of decline in global cognition or any of the specific cognitive domains. Similarly, following correction for multiple testing, there was no association with brain imaging phenotypes or Aβ accumulation. Conclusions:Our results suggest that the summed contribution of LOAD susceptibility loci is not associated with a greater rate of cognitive decline in older adults with T2D, and other pathways may underlie this link.